Perceived risk of developing smoking-related disease among persons living with HIV. Issue 10 (3rd October 2018) - Pacek, Lauren R.; McClernon, F. Joseph; Rass, Olga; Sweizter, Maggie M.; Johnson, Matthew W.
ABSTRACT: Perceived risk of smoking is associated with smoking status, interest in quitting, cessation attempts, and quit success. Research is needed to explore risk perceptions of developing smoking-related disease among persons living with HIV (PLWH). Data came from 267 HIV-positive smokers who completed an online survey assessing perceived health risks associated with (a) generic smoking status; (b) generic non-smoking status; (c) their own personal current smoking; and (d) a hypothetical situation in which they were a non-smoker. PLWH perceived greater risk associated with their current smoking versus hypothetical personal non-smoking ( p' s < 0.001), and greater risks associated with generic smoking status compared with their current smoking ( p' s < 0.001). Being on HIV medication ( β  = 0.65, 95% CI = 0.17, 1.12), interest in quitting smoking ( β  = 0.89, 95% CI = 0.45, 1.32), and having an HIV healthcare provider who has recommended cessation ( β  = 1.04, 95% CI = 0.42, 1.67) were positively associated with perceived risk of developing smoking-related diseases. Findings have implications for developing targeted interventions to correct misperceptions regarding the health risks of smoking among PLWH, a population at particular risk for smoking and smoking-related morbidity and mortality.